A Critical Review of Shopee’s Consumer Compensation Policies: An Indonesian Legal Perspective - Jumiran, Jumiran; Bonggoibo, Alice; Kariadi, Junaedi (Jurnal Ilmu Hukum Kyadiren, 2025)
The rapid growth of e-commerce in Indonesia has led to a significant rise in digital transactions; however, this expansion has not been accompanied by a commensurate advancement in the effectiveness of consumer protection, particularly regarding compensation mechanisms. This study aims to examine the extent to which the compensation system on the Shopee platform safeguards consumer rights both procedurally (in terms of accessibility and transparency) and substantively (in terms of fairness of compensation). It also seeks to identify the power imbalance between business actors and consumers and to evaluate the application of Article 19 of Law Number 8 of 1999 on Consumer Protection within the context of digital transactions. Employing a normative legal approach and qualitative analysis of relevant regulations, platform policies, and user case studies, the study reveals that Shopee’s compensation mechanism remains inadequately transparent and equitable, with significant dominance by business actors. This structural imbalance undermines the effective protection of consumer rights. The findings highlight the urgent need for regulatory reinforcement and the development of a more solution-oriented online dispute resolution framework.